Regular Voluntary Running is Associated with Increased Tumor Vascularization and Immune Cell Infiltration and Decreased Tumor Growth in Mice - Esteves, Mário; Silva, Carina; Bovolini, António; Pereira, Sofia S.; Morais, Tiago; Moreira, Ângela; Costa, Madalena M.; Monteiro, Mariana P; Duarte, Jose Alberto (International Journal of Sports Medicine, 2023)
Tumors present dysfunctional vasculature that limits blood perfusion and hinders immune cells delivery. We aimed to investigate if regular voluntary running promotes tumor vascular remodelling, improves intratumoral immune cells infiltration and inhibits tumor growth. Tumors were induced in C57BL/6 male mice (n=28) by subcutaneous inoculation in the dorsal region with a suspension of RM1 cells (1.5×105 cells/500 µL PBS) and randomly allocated into two groups: sedentary (n=14) and voluntarily exercised on a wheel (n=14). Seven mice from each group were sacrificed 14 and 28 days after cells’ inoculation to evaluate tumor weight, microvessel density, vessels’ lumen regularity and the intratumoral quantity of NKG2D receptors, CD4+and CD8+T cells, by immunohistochemistry. The statistical inference was done through a two-way ANOVA. Exercised mice developed smaller tumors at 14 (0.17±0.1 g vs. 0.48±0.2 g, p<0.05) and 28 (0.92±0.7 g vs. 2.09±1.3 g, p<0.05) days, with higher microvessel density (21.20±3.2 vs. 15.86±4.0 vessels/field, p<0.05), more regular vessels’ lumen (1.06±0.2 vs. 1.43±0.2, p<0.05), and higher CD8+T cells (464.95±48.0 vs. 364.70±49.4 cells/mm2, p<0.01), after 28 days. NKG2D expression was higher in exercised mice at 14 (263.27±25.8 cells/mm2, p<0.05) and 28 (295.06±56.2 cells/mm2, p<0.001) days. Regular voluntary running modulates tumor vasculature, increases immune cells infiltration and attenuates tumor growth, in mice.
Keywords: cancer; physical activity; inactivity; vasculature; immunity